Graph databases: Contextualization and exploratory study - Salgado, Filipe Alexandre Andrade (2018)
After several decades of great success and good services to organizations, relational database technology has been challenged by a new class of database technologies usually called NoSQL (Not only SQL). The recent developments in the area called Big Data contributed decisively to this situation, in which the traditional relational model began to present difficulties, due to the complexity and large volumes of data. Within this new class of databases, different proposals, with several origins and application areas, appeared in four groups, according to their data model: column oriented, document oriented, key-value and Graphs oriented. In particular, graph databases provide a set of characteristics to represent relationships between data that no other model can represent so well. As we live in a world where information is all connected, this database model has what it takes to be successful. In this way, some examples of graph database applications will be discussed as well as demonstrations of the facility to construct queries, which would be extremely complex if they were developed in SQL over relational databases.